A comparison of gravity-driven membrane (GDM) reactor and biofiltration + GDM reactor for seawater reverse osmosis desalination pretreatment - Lee, Seonki (2020)
In this study, permeate quality, membrane performance, and microbial community in a gravity-driven microfiltration (GDM) reactor and a biofiltration (BF) + GDM reactor for seawater reverse osmosis (RO) desalination pretreatment were compared at both lab-scale and pilot-scale. The presence of BF column was more efficient in removing soluble organic substances by biosorption/biodegradation, leading to superior permeate quality from BF + GDM and subsequently lower RO fouling than GDM. Compared to the biofilm-saturated anthracite media, the granular activated carbon media in BF improved the assimilable organic substances removal in BF + GDM. Although less organic substances and microbial cells were accumulated on the membrane in BF + GDM, its permeate flux was 10–20% lower than GDM. Furthermore, BF lowered the amounts and diversity of prokaryotes (due to less organic substances) and eukaryotes (due to BF media rejection and lacking of prokaryotic preys) in the membrane biofilm of BF + GDM, but did not cause significant shifts of predominant species. Thus, the lower flux in BF + GDM was attributed to the limited predation and movement of eukaryotes in membrane biofilm, which may result in the formation of less porous and compact biofilm layer. The cost analysis indicated that BF + GDM-RO requires 5.2% less operating cost and 1.5% less water production cost than GDM-RO.